Q: Simplify this expression 13 plus minus 12 minus minus 5 equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2b

minus 4 plus 9 = 5, so 5x

4p + 9 - 7p + 2 4p - 7p + 9 + 2 p(4 - 7) + 9 + 2 -3p + 11

13+-12--5 = 6

Same as subtracting 6 from 7 = K

Related questions

6

2b

7(3y-2)-(-4y+9)

11p+11

minus 4 plus 9 = 5, so 5x

7g-10h

4p + 9 - 7p + 2 4p - 7p + 9 + 2 p(4 - 7) + 9 + 2 -3p + 11

That will depend on the plus or minus value of 4y in order to simplify the given expression

13+-12--5 = 6

Same as subtracting 6 from 7 = K

To put a plus or minus sign with the digit 5

20a plus 14 will be 34a minus 8a minus 7 34a minus 8 is 26a minus 7 is 19a. The single b is 1b plus 6b which is 7b minus 2b equals 5b.